Complete chloroplast genome sequence of Stachys japonica (Labiatae). Issue 3 (2nd July 2020) - Wang, Mingcheng; Zhao, Qi; Jiang, Dechun; Wang, Zhiqiang
Abstract: The complete chloroplast genome of Stachys japonica was reconstructed by reference-based assembly using Illumina paired-end data. The assembled plastome is 150, 599 base pairs (bp) in length, including a pair of inverted repeat regions (IRs) of 25, 654 bp each, a large single-copy region (LSC) of 81, 701 bp and a small single-copy region (SSC) of 17, 590 bp. A total of 131 genes were predicted from the chloroplast genome, including 86 protein coding genes, 37 tRNA genes and 8 rRNA genes. The overall GC content of S. japonica chloroplast genome was 38.5%. Phylogenetic analysis with several reported chloroplast genomes showed that S. japonica is closely clustered with S. sylvatica . The complete chloroplast genome of S. japonica provides new insight into Labiatae evolutionary and genomic studies.